THE EFFECT OF CORPORATE GOVERNANCE AND AUDIT QUALITY ON TAX AGGRESSIVENESS (An Empirical Study of Companies Listed in the Indonesia Stock Exchange in 2018) - Eka Rofi Mulyana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This research aims to examine the effect of corporate governance and audit quality on tax aggressiveness by examining all companies listed in the Indonesia Stock Exchange (IDX) in 2018. Using purposive sampling, a sample data of 371 companies was acquired. The analysis was performed using multiple linear regression in Statistical Product and Service Solution (SPSS) 24th edition. This reseach finds that tax aggressiveness can be reduced by increasing the number of audit committee and the quality of external audit. Futhermore, tax aggressiveness increases in parallel with the growth of company size, profit, and liquidity. The implication of this researh is to reduce tax aggressiveness by increasing the number of audit committee and improving the quality of external audit. Keywords: Audit Committee, Audit Quality, and Tax Aggressiveness